A equação da violência na escola: análise da produção acadêmica educacional sobre a formação de estudantes LGBTQIA+ (2009 a 2019) - Soares, Cassius Elias de Souza (Universidade do Vale do Rio dos Sinos, 2024)
The present dissertation aims to map, describe and problematize the meanings produced about the relationship between school and violence in the training of LGBTQIA+ students in the context of educational academic production, from 2009 to 2019. The investigation is based on four fields of study: Studies in Teaching, Gender Studies and Cultural Studies, in conjunction with the post-structuralist perspective. By carrying out a meta-research, a set of 16 studies were analyzed and it was identified that, in the context of these completed research, notions contribute to a certain naturalization of violence when addressing the training of LGBTQIA+ students at school. From the description of this certain naturalization produced in the context of research, school violence is problematized in two dimensions. (I) The studies studied discuss that school teachers are not prepared for the issues of confronting violence, ending up reinforcing it. (II) In a second dimension, the works analyzed produce a sense of teacher training equated to an element capable of unequivocally preventing such violence. In this way, when mapping violence at school, the production of knowledge examined seems precisely to reinforce the relationship between school and gender violence that it aims to problematize, which here in the dissertation is called the “equation of violence at school”, in approximation with the language of an arithmetical thought. It is concluded that scientific production questions the violence directed at LGBTQIA+ students, mentioning teacher training to oppose the very idea of violence and, in the way it does so, ends up giving teacher training a salvationist sense in the face of gender violence.

Esta disertación tiene como objetivo mapear, describir y problematizar los sentidos producidos acerca de la relación entre escuela y violencia en la formación de estudiantes LGBTQIA+ en el contexto de la producción académica educacional, en el período de 2009 a 2019. La investigación está sostenida en cuatro campos de estudios: Estudios en Docencia, Estudios de Género y Estudios Culturales, en articulación con la perspectiva postestructuralista. Mediante la realización de una metapesquisa, se analizó un conjunto de 16 estudios y se identificó que, en el contexto de estas investigaciones realizadas, las nociones contribuyen a una cierta naturalización de la violencia al abordar la formación de estudiantes LGBTQIA+ en la escuela. A partir de la descripción de esta cierta naturalización producida en el contexto de la investigación, se problematiza la violencia escolar en dos dimensiones. (I) Los trabajos estudiados argumentan que los profesores y las profesoras de las escuelas no se preparan para las temáticas de enfrentamiento a las violencias, acabando por reforzarlas. (II) En una segunda dimensión, los trabajos analizados producen un sentido de formación docente igualada a un elemento capaz de evitar indiscutiblemente tales violencias. De esa forma, al mapear la violencia en la escuela, la producción de conocimiento examinada parece justamente reforzar la relación entre escuela y violencia de género que objetiva problematizar, lo que aquí en la dissertación se llama de “equación de la violencia en la escuela”, en la aproximación con el lenguaje de un pensamiento aritmético. Se concluye que la produción científica cuestiona las violencias direccionadas a los estudiantes LGBTQIA+, mencionando la formación docente para se oponer a la propia idea de violencia y, del modo como lo hace, acaba por imprimir a la formación docente un sentido salvacionista frente a las violencias de género.
Keywords: Violência; Escola; Gênero; Formação de professores; Estudantes LGBTQIA+; Metapesquisa; Violence; School; Gender; Teacher training; LGBTQIA+ students; Metasearch; ACCNPQ::Ciências Humanas::Educação